The framing of China in Nigeria : an analysis of the coverage of China's involvement in Nigeria by Thisday newspaper - Umejei, Emeka Lucky (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2014)
This study identified the media frames that dominate Thisday newspaper's coverage of China's engagement with Nigeria and relate these frames to frame sponsors, who articulate and contest these framings. Frame analysis is applied to a sample of 40 news, feature and opinion articles between the sample period of 1 November 2011 and 31 December 2012. The study analysed media content from Thisday newspapers, drawing on the four dimensions of frames identified by Entman: define problems, diagnose causes, evaluate causal agents and their effects, and recommend treatment (Entman 1993). Using an inductive approach to frame analysis, the study identified two overarching mega frames, contested among the ruling elites who sponsor their views on China in the media, which define China's engagement with Nigeria; partner/role model and predator. The two mega frames mirror the broad characterisation prevalent in the academic literature on China in Africa. The primary partner/role model mega frame constructs China's engagement with Nigeria as a mutually beneficial economic partnership while on the other hand the predator mega frame constructs it as unequal and exploitative. The study identified the activities of frame sponsors who are articulating and promoting their views on China's engagement with Nigeria in the media as primarily responsible for these framings. The study also identified the activities of frame sponsors (ruling and economic elites) was key to the exclusion of ordinary peoples' voices, civic organisations, trade unions and human rights organisation in the text. However, the study also attributes the exclusion of ordinary voices, human rights, democracy and civic engagements in the text to the weakness of Thisday journalism in mediating the framings of China being promoted and articulated by elite frame sponsors. This is, however, symptomatic of the fault lines of journalism practice in Nigeria.
Keywords: Thisday (Nigeria); Nigeria -- Foreign economic relations -- China; China -- Foreign economic relations -- Nigeria; Journalism -- Nigeria; Journalism -- Political aspects -- Nigeria; Nigerian newspapers -- Objectivity; Social responsibility of business -- Nigeria